Maternal serum selenium as a predictor of preeclampsia - Kaveri, Vismaya; S. K., Manjula; C. N., Sheela; Kurpad, Anura; Dwarkanath, Pratibha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Preeclampsia (PE) is a hypertension disorder condition occurring in 7-10% of all pregnancies. Preeclampsia if unidentified and left untreated is associated with poor maternal and fetal adverse outcomes. The objective of the present study was to characterize maternal serum selenium levels as a predictor of preeclampsia and to correlate dietary selenium intake with serum selenium levels in first trimester of pregnancy Methods: A retrospective case-control study of 107 pregnant women was conducted over 1.5 years at St. John’s Medical College Hospital. On screening for inclusion criteria, at baseline, information on maternal socio-demography, anthropometry, dietary intake and clinical examination was collected. A venous blood sample at baseline and 2nd or 3rdtrimester of pregnancy was collected for estimation of selenium concentrations. Blood pressure was measured at baseline and followed up during pregnancy to select cases and controls. Pregnant women were termed ‘cases’ based on NHBPEP (National High Blood Pressure Education Program) classification and subsequent 22 women with normal blood pressure controlled for age were termed as ‘controls. Results: No statistically significant differences were observed for baseline characteristics, biochemical parameters and blood pressure at recruitment among cases and controls. Cases had significant lower levels of energy (P=0.032) and micronutrients like zinc (P=0.027), selenium (P=0.022), magnesium (P=0.047) at first trimester. The serum selenium levels were significantly higher in cases as compared to the controls (69.2±13.7 vs. 59.6±12.9; P=0.021) at baseline. Conclusions: Our findings suggest that serum selenium levels may not be an independent predictor of preeclampsia. Assessment of other micronutrients, oxidative stress markers and other complementary elements may be useful in predicting preeclampsia.